Chronologic Trends in Studies on Fluoride Mechanisms of Action. (November 2017) - Oh, H.J.; Oh, H.W.; Lee, D.W.; Kim, C.H.; Ahn, J.Y.; Kim, Y.; Shin, H.B.; Kim, C.Y.; Park, S.H.; Jeon, J.G.
Fluoride has been widely used for the prevention of dental caries since the mid-20th century. The aim of this study was to investigate the chronologic trends in studies on fluoride mechanisms of action against dental caries during the years 1950 to 2015. To this aim, queries such as "fluoride, " "fluoride and demineralization, " "fluoride and remineralization, " "fluoride and (plaque or biofilms), " and "fluoride and (bacteria or microbials)" were submitted to PubMed to collect research article information, including titles, abstracts, publication dates, author affiliations, and publication journals. The article information that PubMed produced was then collected by an automatic web crawler and examined through informetrics and linguistic analyses. We found that the number of articles concerned with fluoride mechanisms of action against dental caries was 6, 903 and gradually increased over time during the years 1950 to 2015. They were published by 1, 136 journals—most notably, Caries Research and Journal of Dental Research . Of the articles published, those related to bacteria/microbials had a higher percentage (44%) than those dealing with plaque/biofilms, demineralization, and remineralization. With regard to the geographic distribution of authors, Europe and North America accounted for 65% of the articles during the years 1987 to 2015, although the number of authors in Asia sharply increased in recent years. Among the fluoride compounds, NaF was mentioned more frequently than SnF2, Na2 PO3 F, amine fluoride, and acidulated phosphate fluoride during the years 1986 to 2015. Water fluoridation received the most attention among the various fluoride application methods (toothpastes, mouthwashes, fluoride varnishes, and fluoride gels) during the same period. These results, obtained from employing informetrics and linguistic analyses, suggest that in studies on fluoride mechanisms of action, 1) the unbalanced geographic distribution of articles and 2) the heavy concentration of articles on particular fluoride compounds and application methods should be overcome in future research.